Studies on Anti-Inflammatory, Antioxidant and Free Radical Scavenging of Cu (Ii)-N-Acetyl-Para-Aminophenol (APAP) Based Complex - Ouiza HAMRANI (Journal of Global Pharma Technology, 2019)
N-acetyl-para-aminophenol (APAP) or paracetamol–copper based complex with [Cu(APAP)2(OH)2.H2O] formula and noted Cu-APAP has been synthesized and characterized on the basis of elemental analysis, conductivity, IR and thermal (TG/DTG), NMR and electronic spectral studies. The value of molar conductance of the complex indicates a non-electrolyte nature.The antimicrobial activity of the complex was evaluated against several pathogenic microorganisms to assess its potential. The copper complex was found to be more active against Gram-positive than Gram-negative bacteria. The pharmacological and toxicological ability of the complex were equally explored. The results are compared to those obtained with the unbound drug molecule.The metal complex has been tested for antioxidant and catalase-like activity in order to assess its catalytic properties. The results are encouraging.